Health preservation and enhancement policy-making creation in lithuania as an imperative of the modern society - Danshyna, V. V. (Національний технічний університет "Харківський політехнічний інститут", 2019)
The study aims. The aim is to analyze and present the assumptions and conceptual direction of Lithuania’s healthy lifestyle and health sustainability policy formulation and implementation.
Keywords: healthy lifestyle; health-saving policies